Effects of Hydroxyurea on Skeletal Muscle Energetics and Function in a Mildly Anemic Mouse Model - Michel, Constance P.; Messonnier, Laurent A.; Giannesini, Benoit; Chatel, Benjamin; Vilmen, Christophe; Le Fur, Yann; Bendahan, David (Frontiers in Physiology, 2022)
Hydroxyurea (HU) is a ribonucleotide reductase inhibitor most commonly used as a therapeutic agent in sickle cell disease (SCD) with the aim of reducing the risk of vaso-occlusion and improving oxygen transport to tissues. Previous studies suggest that HU may be even beneficial in mild anemia. However, the corresponding effects on skeletal muscle energetics and function have never been reported in such a mild anemia model. Seventeen mildly anemic HbAA Townes mice were subjected to a standardized rest-stimulation (transcutaneous stimulation)-protocol while muscle energetics using 31Phosphorus magnetic resonance spectroscopy and muscle force production were assessed and recorded. Eight mice were supplemented with hydroxyurea (HU) for 6 weeks while 9 were not (CON). HU mice displayed a higher specific total force production compared to the CON, with 501.35 ± 20.45 N/mm3 and 437.43 ± 20.18 N/mm3 respectively (+ 14.6%, p < 0.05). Neither the total rate of energy consumption nor the oxidative metabolic rate were significantly different between groups. The present results illustrated a positive effect of a HU chronic supplementation on skeletal muscle function in mice with mild anemia.